Help is on hand: Can AI help ease the burden of research communications? - TATTERSALL, Andy (Institutional Knowledge at Singapore Management University, 2023)
We have long known about AI, largely through science fiction films, but now in 2023 it feels like it has truly arrived. The implications for academia are truly far reaching, from information governance to ethics, from assessment to systematic reviews. It is inevitable that AI will soon become commonplace across the research cycle, including scholarly communications and dissemination. The question is, how useful will it be and can it help broaden the reach and impact of research outputs? Already there are signs that AI could become a useful tool in sharing research and knowledge. This short talk will talk about some of the opportunities as well as pitfalls as we take the next technological step forward.